The Impact of Background Knowledge Input on the Development of English Writing Skills Among University Students - SUN, YAJIE (Pacific International Journal, 2025)
In recent years, Chinese university students studying English have shown notable improvements in their writing skills. However, without mastering the relevant cultural context, their writing cannot achieve optimal effectiveness.This paper examines the challenges Chinese college students face in English writing and argues that insufficient background knowledge of the target language’s culture hampers their performance. Current writing often reflects mother-tongue thinking, leading to “Chinese-style English” and structural mismatches between Chinese and English discourse. The study highlights the importance of cultural awareness as an integral component of comprehensive language competence and reviews how domestic English textbooks increasingly embed cultural information. To enhance students’ writing, the paper proposes several strategies. By enriching input and fostering a British style linear discourse mode, learners can develop clearer focus, better coherence, and more authentic expression in English compositions. The findings suggest that systematic enrichment of cultural background knowledge is essential for improving Chinese students’ English writing proficiency.